2021
DOI: 10.1101/2021.09.17.21263549
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A systematic review of COVID-19 vaccine efficacy and effectiveness against SARS-CoV-2 infection and disease

Abstract: Billions of doses of COVID-19 vaccines have been administered around the world, dramatically reducing SARS-CoV-2 incidence in some settings. Many studies suggest vaccines provide a high degree of protection against infection and disease, but precise estimates vary and studies differ in design, outcomes measured, dosing regime, location, and circulating virus strains. Here we conduct a systematic review of COVID-19 vaccines as of August 2021. We included efficacy data from Phase 3 clinical trials for 13 vaccine… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
50
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(56 citation statements)
references
References 237 publications
(228 reference statements)
1
50
0
1
Order By: Relevance
“…A systematic review including studies up to mid-August, 2021, identified 21 efficacy trials and 58 vaccine effectiveness studies of COVID-19 vaccines, most from high-income countries. 19 Despite the short time window of 21 days between first and second doses used in vaccine trials and by many countries, single-dose efficacy and effectiveness against severe disease for mRNA (60–90% for BNT162b2; 75–80% for mRNA1273) and adenoviral vector vaccines (75–100% for ChAdOx1; 85% for Ad26.COV2) was high, but lower for inactivated viral vaccines (37–46% for CoronaVac). 19 In Canada, where longer intervals to the second dose were routine, first dose vaccine effectiveness of mRNA vaccines was highest more than 35 days after receipt in all age groups.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…A systematic review including studies up to mid-August, 2021, identified 21 efficacy trials and 58 vaccine effectiveness studies of COVID-19 vaccines, most from high-income countries. 19 Despite the short time window of 21 days between first and second doses used in vaccine trials and by many countries, single-dose efficacy and effectiveness against severe disease for mRNA (60–90% for BNT162b2; 75–80% for mRNA1273) and adenoviral vector vaccines (75–100% for ChAdOx1; 85% for Ad26.COV2) was high, but lower for inactivated viral vaccines (37–46% for CoronaVac). 19 In Canada, where longer intervals to the second dose were routine, first dose vaccine effectiveness of mRNA vaccines was highest more than 35 days after receipt in all age groups.…”
mentioning
confidence: 99%
“… 19 Despite the short time window of 21 days between first and second doses used in vaccine trials and by many countries, single-dose efficacy and effectiveness against severe disease for mRNA (60–90% for BNT162b2; 75–80% for mRNA1273) and adenoviral vector vaccines (75–100% for ChAdOx1; 85% for Ad26.COV2) was high, but lower for inactivated viral vaccines (37–46% for CoronaVac). 19 In Canada, where longer intervals to the second dose were routine, first dose vaccine effectiveness of mRNA vaccines was highest more than 35 days after receipt in all age groups. 20 Another Canadian study found high vaccine effectiveness was maintained up to 4 months after a single dose of an mRNA vaccine.…”
mentioning
confidence: 99%
See 3 more Smart Citations